Challenges for health care providers, parents and patients who face a child hood cancer diagnosis in Zambia - Mulima Walubita; Bornwell Sikateyo; Joseph M. Zulu (BMC, 2018)
Abstract Background Zambia is experiencing high prevalence of childhood cancer. However, very few children access and complete treatment for cancer. This study aimed to document the challenges for health care providers, parents and patients who face a child hood cancer diagnosis in Zambia, and their coping strategies. Methods This was an exploratory health facility-based qualitative study that was conducted at a Paediatric oncology ward at referral hospital in Zambia. In-depth individual interviews conducted with fifteen (15) caregivers and seven (7) key informants were analysed using thematic analysis. Results Several challenges related to managing the childhood cancer diagnosis were recorded. Individual and family challenges were inadequate knowledge on childhood cancer, lack of finances to meet treatment and transport costs as well as long period of hospitalisation that affected women's ability to perform multiple responsibilities. Whereas challenges at community level were inadequate support to address emotional and physical distress and social stigmatisation experienced by caregivers. Health systems issues included inadequate specialised health workers, poor communication among health workers, limited space and beds as well as insufficient supplies such as blood. Cultural related factors were the belief that cancer is a product of witchcraft as well as religious beliefs regarding the role of faith healing in childhood cancer treatment. Coping strategies used by parents/ caregivers included praying to God, material support from organisations and church as well as delaying having another child. Conclusion Addressing the challenges for health care providers, parents and patients who face a childhood cancer diagnosis may require adopting a systems or an ecological approach that allows developing strategies that simultaneously address challenges related to the individual, family, community, health system and cultural aspects.